Strategic Inattention, Inflation Dynamics, and the Non-Neutrality of Money - Hassan Afrouzi (Center for Economic Studies and ifo Institute (CESifo), 2020)
How does competition affect information acquisition of firms and thus the response of inflation and output to monetary policy shocks? This paper addresses these questions in a new dynamic general equilibrium model with both dynamic rational inattention and oligopolistic competition. In the model, rationally inattentive firms acquire information about the endogenous beliefs of their competitors. Moreover, firms with fewer competitors endogenously choose to acquire less information about aggregate shocks – a novel prediction of the model that is supported by empirical evidence from survey data. A quantitative exercise disciplined by firm-level survey data shows that firms' strategic inattention to aggregate shocks associated with oligopolistic competition increases monetary non-neutrality by up to 77% and amplifies the half-life of output response to monetary shocks by up to 30%. Furthermore, the model matches the relationship between the number of firms' competitors and their uncertainty about inflation as a non-targeted moment.
Keywords: E31; E32; E71; 330; rational inattention; oligopolistic competition; inflation dynamics; inflation expectations; monetary non-neutrality